A Borrowed Cipher for a Top-Secret Letter Written by Frederick of Aragon King of Naples to the Catholic Kings in the BnF, Espagnol 318 (Studi di storia medioevale e di diplomatica - Nuova Serie, 2020)
This article presents the deciphering, as well as the reconstruction of the related historical contest, of an encrypted letter written by Frederick King of Naples to the Catholic kings, preserved in the ms. Espagnol 318 of the BnF. The cypher at the disposal of Joan Ram Escrivà, the Spanish Ambassador in Naples at the time, was unusually used for its encryption.
Keywords: Early-Modern History; Diplomacy; Criptography; Spain; Naples; 15th Century